Jukebox - Chanani, Nidhi (First Second, 2021)
While Shaheen is investigating her father's disappearance, a mysterious jukebox magically transports her and her cousin Tannaz to different decades based on the music it's playing, from political marches to landmark concerts. The two girls must find Shaheen's dad before the music stops.